Demonisasi Islam dalam Film ˜Tanda Tanya (?)™ - Ritonga, Rajab (LP2M ISBI Bandung, 2013)
ABSTRACT ˜Tanda Tanya (?)™ movie has become an Indonesian cinematic work with some controversies complement with it. The controversies lie on how the movie constructed their messages related to the description of Islamic image. The Islamic image which is depicted in this movie contains several sym- bols which created a demonization on the construction of Islam and Moslem. The narrative theory that has been employed focuses on greimas actantial analysis models which emphasizes on how the narrative creates a story and how the story becomes a narrative discourse. The semiotic analysis used on this research is in term of constructivist perspective which aims at constructing the phenomena as a whole answer. The result of the research is that demonization of Islam has been constructed through the narrative sequences of ˜Tanda Tanya™. The movie depicted Islam in an image of traditional, un- civilized, terrorism, destructive, and aggressive community. This created a meaning of Islam as a negative and demonic community, religion, and value. Keywords: demonization, Islam, narrative ABSTRAK Film ˜Tanda Tanya (?)™ merupakan sebuah karya cinema Indonesia yang mengundang banyak kontroversi. Kontroversi terletak pada bagaimana film ini mengkonstruksikan pesan-pesannya terkait penggambaran citra Islam. Citra Islam yang digambarkan dalam film ini mengandung simbol-simbol yang menciptakan sebuah demonisasi pada kon- struksi Islam dan muslim. Dalam penelitian ini teori naratif digunakan sebagai alat un- tuk memberikan gambaran tentang fenomena demonisasi. Teori naratif yang digunakan berfokus pada model analisis aktansial greimas yang menitikberatkan bagaimana naratif menciptakan sebuah cerita dan bagaimana cerita menjadi sebuah wacana naratif. Analisis semiotik yang digunakan dalam penelitian ini berdasarkan penggunaan dalam paradigma konstruktivis yang bertujuan mengkonstruksi fenomena sebagai sebuah jawaban. Temuan penelitian ini ialah demonisasi umat Islam dikonstruksikan melalui sekuen/babakan nara- tif dalam film ˜Tanda Tanya™. Film ini menggambarkan Islam dalam sebuah citra masyara- kat yang tradisional, tidak beradab, teroris, merusak, dan agresif. Ini menciptakan suatu pemaknaan Islam sebagai masyarakat, agama, dan nilai yang demonik dan negatif. Kata kunci: demonisasi, Islam, naratif